Reinforcement Design Algorithm For Concrete Shells - Fahmi, Hani M.; Ali, Nabil M. (Nahrain University College of Engineering Journal)
The absence of universally accepted solutions in the structural concrete codes for the design of reinforcement in shells gives rise to the problem of calculating the required reinforcement in these structures. The constant development of the computer s performance and storage capacity combined with thepowerful numerical methods reveal the need for a standard procedure to design shells subjected to membrane and flexural forces. In this paper, the solution for the design of the required reinforcement in concrete shells is presented based on a complete iterative computational algorithm to design shell elements subjected to combined membrane forces and bending moments. In the design equations, the reinforcement will contribute to tension and the concretecompression struts parallel to the crack direction will contribute to compression. The reinforcement is assumed to have two orthogonal layers placed in the top and bottom surfaces with appropriate covers. Each reinforcement layer has reinforcing bars placed orthogonally. For the concrete compressionstruts, the stress is assumed to be uniformly distributed in the depth of Whitney s stress block. This design algorithm is achieved by developing a design code (DRCSH) based on a complete iterative computational algorithm. This program can be used as a stand-alone version, to determine the load carryingcapacity of critical points in reinforced concrete panels, plates and shells; and to verify the design code on the element level, five experimental models are designed. The designed elements give calculated ultimate strengths from 7 to 18% higher than test results values, except one model, which confirms theadequacy of the design algorithm, and the developed design code.